Entertaining television the BBC and popular television culture in the 1950s - Holmes, Su 1976- (Manchester Univ. Press, 2008)
This text makes a seminal contribution to British television history by focusing on the 'beginnings' of popular generic forms, such as soap operas, quiz/game shows and 'problem' shows. Su Holmes demonstrates how BBC television played an important role in developing these popular generic forms.
Includes bibliographical references (p. [207]-217) and index
Keywords: British Broadcasting Corporation / History; British Broadcasting Corporation -- History; British Broadcasting Corporation; Geschichte 1900-2000; Geschichte 1950-1960; Television broadcasting / Great Britain / History; Popular culture / Great Britain / History / 20th century; Geschichte; Popular culture -- Great Britain -- History -- 20th century; Television broadcasting -- Great Britain -- History; Fernsehsendung; Unterhaltungssendung; Großbritannien